Definition of properties and characteristics of common BIM Components from EnergyPlus - Sérgio Leal Ferreira (Gestão & Tecnologia de Projetos, 2015)
The Brazilian Association of Technical Standards is making an effort since 2009 to standardize necessary elements to a well-done development of the Building Information Modeling (BIM) in Brazil. Among these efforts, it was recently created a workgroup with the purpose of give support to the industry in the creation of BIM components that contain properties and data necessary to an efficient modeling. Consequently, these components will be ready to be used in specific analyses. One of the predicted analyses is Building Energy Efficiency. Building Energy Software Tools Directory provides information about 417 building software tools for evaluating energy efficiency, and EnergyPlus is the best alternative presented. This work shows the results of the EnergyPlus data analysis in the field of the most common components in architecture, like doors and windows, and demonstrates the pathway inside the Input Data Dictionary to find all linked data to the objects used in the input data file. As a result, it will be presented the information extracting method and the discussions about the application of the method to extract information about all other components included in the BIM model.